Field‐Effect Transistors: A Cofacially Stacked Electron‐Deficient Small Molecule with a High Electron Mobility of over 10 cm2 V−1 s−1 in Air (Adv. Mater. 48/2015). (December 2015) - Dou, Jin‐Hu; Zheng, Yu‐Qing; Yao, Ze‐Fan; Lei, Ting; Shen, Xingxing; Luo, Xu‐Yi; Yu, Zhi‐Ao; Zhang, Shi‐Ding; Han, Guangchao; Wang, Zhi; Yi, Yuanping; Wang, Jie‐Yu; et al.
Abstract : Compared with abundant p‐type organic semiconductors with high mobilities, n‐type semiconductors with mobilities over 1 cm 2 V −1 s −1 are rare. On page 8051, Y. Yi, J. Pei, and co‐workers report a new small molecule, F4‐BDOPV, with unprecedentedly high electron mobilities of up to 12.6 cm 2 V −1 s −1 . This is the first time that air‐stable n‐type organic semiconductors have shown mobilities surpassing 10 cm 2 V −1 s −1, an important benchmark for practical applications.